DETERMINANTS OF EFFECTIVENESS REPAYMENT APPS AT P2P LENDING PLATFORM DURING COVID 19 PANDEMIC IN INDONESIA - Kurniasari, Florentina; Utomo, Prio (Universitas Multimedia Nusantara, 2021)
Abstract” The advance of technology development today brings an innovation in the financial industries all across the world, including in Indonesia. The financial technology continues to emerge from the sector of payment, investment and loans online or as we are familiar with the term P2P Lending platform. But, the growth of this business had a challenge when the Covid-19 Pandemic hit the country in the early 2020. The P2P lending platform experienced the first highest default rate due the difficulties of the SME's as its major customers' in repaying their loans. The purpose of this research is to analyze the determinants of effectiveness repayment apps for ultra-micro segment on P2P platform in Indonesia. As a quantitative research, primary data were collected through questionnaire answered by 133 respondents who were borrower of the P2P lending platform. The data collection was furthered processed statistically using Structural Equation Method (SEM). The study showed that the repayment decision had significantly influenced by perceived usefulness, perceived ease of use, perceived risk and information quality. Information quality itself had the highest influenced among others. Keywords: Perceived Usefulness; Perceived Ease of Use; Information Quality; Perceived Risks; Repayment Decision; Repayment Apps